Coronary Artery Calcification Score as a Predictor of All-Cause Mortality and Cardiovascular Outcome in Peritoneal Dialysis Patients. Issue 2 (March 2016) - Xie, Qionghong; Ge, Xiaolin; Shang, Da; Li, Yun; Yan, Huanqing; Tian, Jing; Hao, Chuan-Ming; Zhu, Tongying
Background: This study aimed to examine whether the coronary artery calcification score (CaCS) was associated with the prognosis of peritoneal dialysis (PD) patients. Methods: Adult PD patients who were clinically stable for at least 2 months were recruited for this prospective, observational cohort study. Coronary artery calcification was assessed using multislice spiral computed tomography and was recorded according to the Agatston score. The end-points including all-cause mortality, cardiovascular events, and cardiovascular mortality were assessed. Multivariate Cox regression was used to identify independent predictors of all-cause mortality, cardiovascular events (CVEs), and cardiovascular mortality. Results: A total of 179 PD patients (86 men) with a mean age of 63.5 ± 14.8 years were recruited for this study. Coronary artery calcification scores ranging from 0 to 5, 257 were stratified as follows: no (CaCS = 0, n = 54), low (0 < CaCS < 400, n = 72), and high (CaCS ≥ 400, n = 53) calcification. The follow-up duration was 30.6 ± 16.2 (24 – 63) months. Compared with the no calcification group, patients with a higher CaCS were older and had lower diastolic blood pressure, residual renal function, and serum albumin, and higher HbA1 C and serum insulin. Multivariate Cox regression revealed that the CaCS was an independent predictor for all the 3 endpoints after adjustment in PD patients. Conclusions: CaCS was an independent predictor of all-cause mortality, cardiovascular events, and cardiovascular mortality in patients receiving peritoneal dialysis.